In defense of the coffeehouse chains in Türkiye: finding a silver lining amidst misinformation, disinformation, manipulation and social unrest - Aykut Sığın (Cogent Social Sciences, 2025)
Protests started all over the world in the last quarter of 2023 after Israel launched an aerial bombardment campaign on Gaza. Türkiye was one of the countries where large-scale protests against Israel took place. Organized and individual street protests as well as campaigns for boycotting Israeli products were initiated. Protesters went to Starbucks stores to tell customers to reconsider drinking Starbucks coffee after the company stated it would sue its union for announcing its support for Palestine. Casualties occurred despite statements from the Turkish branch of the company regarding their neutrality in political issues. I attempt to discuss that the nature of these attacks is anti-Western, rather than anti-Zionist by tracing the politics of coffee, coffeehouse chains and the public sphere. I conclude that coffeehouse chains, especially Starbucks, function as iconic carriers of Western values but they should be seen as a global cultural phenomenon in a rapidly changing world.